Factors controlling volatile organic compounds in dwellings in Melbourne, Australia. (9th April 2015) - Cheng, M.; Galbally, I. E.; Molloy, S. B.; Selleck, P. W.; Keywood, M. D.; Lawson, S. J.; Powell, J. C.; Gillett, R. W.; Dunne, E.
Abstract: This study characterized indoor volatile organic compounds (VOCs) and investigated the effects of the dwelling characteristics, building materials, occupant activities, and environmental conditions on indoor VOC concentrations in 40 dwellings located in Melbourne, Australia, in 2008 and 2009. A total of 97 VOCs were identified. Nine VOCs, n‐butane, 2‐methylbutane, toluene, formaldehyde, acetaldehyde, d‐limonene, ethanol, 2‐propanol, and acetic acid, accounted for 68% of the sum of all VOCs. The median indoor concentrations of all VOCs were greater than those measured outdoors. The occupant density was positively associated with indoor VOC concentrations via occupant activities, including respiration and combustion. Terpenes were associated with the use of household cleaning and laundry products. A petroleum‐like indoor VOC signature of alkanes and aromatics was associated with the proximity of major roads. The indoor VOC concentrations were negatively correlated ( P < 0.05) with ventilation. Levels of VOCs in these Australian dwellings were lower than those from previous studies in North America and Europe, probably due to a combination of an ongoing temporal decrease in indoor VOC concentrations and the leakier nature of Australian dwellings.